From single to multi-stage forming process of copper thin sheet - Lagroum Amine; Manach Pierre-Yves; Thuillier Sandrine (Mechanics & Industry)
In the electronics industry sector, different types of parts made out of copper alloys are used, such as metal supports (lead frames), on which the chips are assembled. These parts are produced using progressive dies, with several blanking and bending stages. There is a huge interest to numerically predict these multistage forming processes, to decrease design time and to anticipate production problems such as non-compliance with dimensional tolerances depending on the material used. This paper deals with the progressive forming of copper parts with single and multi-stage process coupled with experimental and numerical approaches for bending operations. The main contribution of this study is the design of a single stage bending tool for rectangular samples representative of multi-stage industrial processes, providing a relevant experimental database for numerical model validation. This device is based on the technology of progressive dies, though it allows the production of one part at a time. Instrumentation provides local load and displacement and an experimental database is built for Cu-ETP R290 copper strip. A multi-stage bending industrial process dedicated to the manufacturing of electrical contacts is also considered in this study. Numerical models of both single and multi-stage processes are developed, with a focus on the technological importance of a cam slider for the industrial process. The results show that the bending force is mainly influenced by the sample width. In addition, numerical models for the rectangular geometries capture some of the trends from the experiment such as the proportionality of the maximum force with the bent width. Overall, the models are able to predict springback within the process tolerance. Finally, comparison of one stage of the bending sequence with the single stage bending model showed that the single model approach gives similar results in terms of load and plastic deformation.